1970
DOI: 10.3126/sw.v8i8.3855
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Monitoring of Galvanized Steel in Simulated Wet-Dry Cyclic Condition in 0.05 M NaCl Solution

Abstract: Abstract:The corrosion monitoring of galvanized steel in 1 h wet and 7 h dry cyclic condition in 0.05 M NaCl has been carried out using AC impedance technique. During the wet-dry cycles, the polarization resistance, R p , and solution resistance, R s , were continuously monitored. The instantaneous corrosion rate of the coating was estimated from the obtained R p -1 and time of wetness (TOW) was determined from the R s values. The corrosion potential, E corr , was measured twice a day during the immersion peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A positive shift of the E corr due to the presence of Equisetum arvense extract indicated that this organic compound is an effective suppressor of the anodic dissolution reaction, which could be related to the formation of a protective layer . On the other hand, the negative shift of E corr indicated the acceleration of anodic dissolution of the oxide layer . The parameters of E corr and I corr were determined by extrapolation of the cathodic polarization curve and anodic polarization curve, and IE cpt was calculated from the following equation: IEcpttrue(%true)=true[1(Icorr/Icorr0)true]×100 where I 0 corr and I corr are corrosion current densities in absence and presence of Equisetum arvense extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive shift of the E corr due to the presence of Equisetum arvense extract indicated that this organic compound is an effective suppressor of the anodic dissolution reaction, which could be related to the formation of a protective layer . On the other hand, the negative shift of E corr indicated the acceleration of anodic dissolution of the oxide layer . The parameters of E corr and I corr were determined by extrapolation of the cathodic polarization curve and anodic polarization curve, and IE cpt was calculated from the following equation: IEcpttrue(%true)=true[1(Icorr/Icorr0)true]×100 where I 0 corr and I corr are corrosion current densities in absence and presence of Equisetum arvense extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[20] On the other hand, the negative shift of E corr indicated the acceleration of anodic dissolution of the oxide layer. [21] The parameters of E corr and I corr were determined by extrapolation of the cathodic polarization curve and anodic polarization curve, and IE cpt was calculated from the following equation [22] :…”
Section: Resultsmentioning
confidence: 99%